EKONOMI BERKELANJUTAN: KUNCI KETAHANAN PANGAN DAN KEMAJUAN INDONESIA EMAS DI IKN - Effendi Rusdiana, Dedy; Saputra, Wahyu; Yanti, Nur (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
By 2045, Indonesia's ambition is to become a developed country on par with superpowers. In this context, the importance of a sustainable economy as the foundation for achieving this goal becomes increasingly clear. With a focus on food security, this article identifies the multidimensional challenges facing Indonesia. In order to understand the role of a sustainable economy, the article highlights the principles of food self-reliance and food sovereignty that underpin national food policy. As such, it provides a foundation for a deeper understanding of Indonesia's efforts in realizing sustainable food security as an integral part of the country's vision for progress by 2045. Keywords: food security, sustainable economy, Indonesia Emas, IKN, green economy